Nanotechnology meet phytomedicine towards smarter drug delivery system. - Prof. (Dr)Mohd. Wasiullah; Prof. (Dr) Piyush Yadav; Amit Kannaujiya (International Journal of Toxins and Toxics, 2026)
Using bioactive substances derived from plants, or phytomedicine, has long shown promise in treating a variety of illnesses with fewer adverse effects than synthetic medications. Nevertheless, a lot of phytochemicals have issues with inadequate targeting in vivo, low bioavailability, poor solubility, and chemical instability. By enabling encapsulation, controlled release, targeted delivery, and stimuli responsive behavior, nanotechnology provides effective tools to get around these restrictions. This review examines the intersection of nanotechnology and phytomedicine, providing an overview of recent developments in nanocarrier systems, including micelles, lipid-based nanoparticles, polymeric nanoparticles, nanoemulsions, and hybrid materials, intended for the intelligent delivery of therapeutic agents derived from plants. We look at how these nano-formulations reduce off-target effects, improve pharmacokinetics, increase therapeutic efficacy, and enable controlled or triggerable release in response to environmental ues (pH, redox, enzymes, etc.). We also discuss important issues like cost, regulatory barriers, manufacturing scalability, and safety/toxicity. Lastly, we point out potential future paths that could result in the next generation of intelligent phytomedicine delivery systems, such as theranostics, green synthesis, and AI-guided design.
Keywords: Nanocarrier; Nanoemulsions; Phytomedicine; bioavailability; nanotechnology